Impact of inter-organizational and extraorganizational factors on the policies of Science and Technology Parks in emerging economies (2021)
This article aims to study policymaking resulting from the impact of intra- and extra-organizational factors of science and technology parks (S&T parks). This article is classified as applied in terms of objective and quantitative in terms of data gathering. The population comprises senior managers of companies established in the five selected S&T parks, totaling 493. Applying the stratified random sampling method and the Cochran formula, the sample size was determined at 216. The validity of the questionnaire’s content was endorsed by professors, experts and pundits. The Cronbach’s alpha of the questionnaire was extracted to be higher than endorsed levels in all dimensions, which shows the reliability of the research. Results show that intra-organizational factors (organizational, networking, legal and fiscal), with the intervention of extra-organizational factors (institutional, cultural and contextual, capital and location), lead to development of six S&T park policymaking categories (policymaking for culture and motivation, policymaking for creation of incentives, policymaking for development of capacity and capability, policymaking for infrastructure, policymaking for attracting investment, policymaking for creating business opportunities).